Variación de las cuentas por cobrar de la Cooperativa de Ahorro y Crédito Lucha Campesina sucursal Baba entre los semestres del año 2024. - Barboto Tóala, Jhonny Daniel (2024)
Financial institutions in Ecuador play an important role in society, however, there are different problems that interrupt their correct functioning, one of them is the variation in accounts receivable, for that reason in this case study it is proposed to examine the Accounts Receivable of the Savings and Credit Cooperative "Lucha Campesina" located in the Baba canton of the province of Los Ríos in order to recognize and analyze the variations in its Accounts Receivable during the first and second semester of 2024 and in turn determine the different economic factors that influence the company's liquidity.